EEG and MR Spectroscopy in Hypoxic-Ischemic Encephalopathy in Term Newborns - J Gordon Millichap (Pediatric Neurology Briefs, 2010)
Researchers from the University of Bologna, Italy, studied the relation of amplitude integrated EEG findings in the first 24 hrs of life to brain metabolic changes, detected by proton MR spectroscopy (H-MRS) at 7-10 days of life, in 32 term newborns with hypoxic-ischemic encephalopathy (HIE).